Developing Timor-Leste’s coastal economy: assessing potential climate change impacts and adaptation options. Final report to the Australian Government Coral Triangle Initiative on Coral Reefs, Fisheries and Food Security National Initiative - Mills DJ; Abernethy, K.A.; King, J.; Hoddy ET; Teoh, Shwu Jiau; Larocca P; Gonsalves, D.; Fernandes, A.; Park, Sarah E. (WorldFish, 2013)
This report details activities carried out by WorldFish, the National Directorate of Fisheries and Aquaculture, local partners and communities for the project, ‘Developing Timor-Leste’s coastal economy: Assessing potential climate change impacts and adaptation options’. Central to the project was participatory community adaptation planning. The focus was on coastal fishing/agricultural communities, resource issues (land, sea, water), and challenges to associated seasonal livelihoods. Gender was mainstreamed throughout the project.